(untitled) (Journal of the College of Basic Education, 2022)
Thank God, the Lord of the Worlds, and peace and prayer supplication on the ring of the prophets and the missionaries Muhammad, and to God and his good friends: The research tagged the methods of teaching the prophetic biography is an effort that adds to the world of knowledge an art of teaching, as the researcher prepared the Quran as its main source to present the prophetic biography because of the characteristics of this method and show the importance of this subject to students of science or teachers, as such topics of a cultural nature, In addition, it will present the historical importance and prophetic truths through downloading and the biography of Mustafa al-Muta’a, and the methods used by Mustafa in teaching Muslims and benefiting from them in teaching and in preparing modern educational methods in teaching the prophetic biography. The details of his research are based on the following headings: The first topic: the definition of the search and it was on two demands The first requirement: the importance of research and its purpose The second requirement: defining terms The second topic: the objectives of the prophet’s biography and its impact on the individual and society have also included two demands: The first requirement: the objectives of the Prophet’s biography The second requirement: the impact of the prophet’s biography on the individual and society The Third Topic: The Foundations and Methods of Teaching the Prophet’s Biography The first requirement: the foundations of teaching the prophet’s biography The second requirement: the methods of teaching the Prophet’s biography The third one. A typical lesson in teaching the prophetic biography according to the style of the story or description